Do The Financial Reports of Troubled Banks Meet the Qualitative Characteristics of Financial Reports? - Ashari, Hasan; Nugrahanti, Trinandari Prasetyo (Universitas Pendidikan Indonesia, 2024)
This study aims to analyze whether the financial reports of Rural Banks (BPR) that are included in Banks Under Recovery/BDP (Before called the Bank under Intensive Supervision/BDPI and the Bank under Special Supervision/BPDK) meet the qualitative characteristics of financial statements. This study uses the financial statement ratio of the BPRs whose business permit is revoked by the Financial Services Authority up to 2023. The samples used are 47 banks from 127 banks that had been revoked. Meanwhile, a healthy bank sample was 171 BPRs in 2016-2019. Correlation analysis is used in this study. The results of this study concluded that the troubled BPRs financial statements did not meet the qualitative characteristics of financial statements. Only one in 47 BPRs meets the qualitative characteristics of financial statements. This was evidenced by comparing the financial ratio of the troubled bank with a healthy bank, such as NPLs, BOPO, LDR, CAR, and ROA showed negative results (different directions) or the level of relationship of more than one level. The author suggests the regulator so that financial ratios in the financial statements that indicate the bank's health can be used as the initial data analysis of BPRs governance implementation.